Rancang Bangun Aplikasi Penjualan dan Persediaan Obat pada Apotek Berbasis Android - Asri Mulyani; Yosep Septiana; Rizky Helmi (Institut Teknologi Garut, 2022)
Management of sales and inventory is very important for a business entity, for example in a pharmacy engaged in the pharmaceutical trade with a good process of managing sales and monitoring of drugs that will provide a maximum increase in profits and can reduce the risk of losses due to miscalculations at the pharmacy, so that the process sales and inventory run effectively and efficiently. we need a system that helps manage sales, monitor sales, and monitor drug supplies quickly and precisely. Based on these problems, the purpose of this research is to design and build an application for selling and supplying drugs at an android-based pharmacy that is carried out at the Tanjung Farma Garuti pharmacy. The system development method used is Extreme Programming (XP) with the stages of Planning, Design, Coding, and Testing. For modeling the system used is the Unified Modeling Language (UML) with diagrams used use case diagrams, activity diagrams, sequence diagrams. The application will be developed based on Android. The results of this study are in the form of an application that can make it easier for pharmacy employees to make notes to manage sales data and check/monitor drugs as well as to provide facilities for the Tanjung Farma pharmacy to improve service to the needs of drugs to the public.